I never knew that about England - Winn, Christopher, 1958- 2005 (London : Ebury Press, 2005)
Crammed with facts and information, this work celebrates England, the places and people that make this country unique, and includes history, legends, firsts, supremes, unusuals, inventions, birthplaces and gossip.Includes index.Crammed with facts and information, this work celebrates England, the places and people that make this country unique, and includes history, legends, firsts, supremes, unusuals, inventions, birthplaces and gossip.
'Discover hundreds of facts you never knew about England in this fascinating miscellany'--Jacket.
Includes index.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: England -- Miscellanea; England -- History; England -- Description and travel